Choice of radiography in orthodontic treatment on children and adolescents: A questionnaire‐based study performed in Sweden. (6th June 2021) - Stervik, Christina; Lith, Agneta; Westerlund, Anna; Ekestubbe, Annika
Abstract: The aim was to investigate the objective and choice of different radiographic examinations used in orthodontic treatment of children and adolescents, using a web‐based questionnaire directed toward specialists in orthodontics. The questionnaire was distributed to 255 orthodontists in Sweden. In total, 142 responses were received, and 11 specialists were interviewed. Questions were related to the use of radiography during different treatment stages; modifications to the treatment regimen owing to radiographic findings; and the use of and/or need for guidelines in radiography. Radiographic examinations were performed in all treatment stages and mainly during treatment planning. Panoramic radiographs were always or often used by the respondents (99%), less frequently used were lateral radiographs (66%) and intra‐oral radiographs of the incisor regions (69%). Cone beam computed tomography (CBCT) was sparsely employed. A majority of the respondents considered that radiographic findings often or occasionally affected the treatment. Local‐ or clinic‐specific guidelines were used by 85% of respondents. The need for national guidelines was considered low. The frequent use of panoramic radiography together with application of local guidelines, may indicate that radiographic selection criteria are not individualised. National guidelines might facilitate updates on radiographic techniques, and on radiation doses and risks in young patients.